Nano-Azo Ligand and Its Superhydrophobic Complexes: Synthesis, Characterization, DFT, Contact Angle, Molecular Docking, and Antimicrobial Studies. (23rd October 2020) - Mohamed, Gehad G.; Mahmoud, Walaa H.; Refaat, Ahmed M.
Abstract : Metal complexes of the 2, 2'-(1, 3-phenylenebis(diazene-2, 1-diyl))bis(4-aminobenzoic acid) diazo ligand (H2 L) derived from m -phenylenediamine and p -aminobenzoic acid were synthesized and characterized by different spectral, thermal, and analytical tools. The H2 L ligand reacted with the metal ions Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II), and Cd(II) as 1 : 1 stoichiometry. All complexes displayed an octahedral geometry according to the electronic and magnetic moment measurements. The IR spectra revealed the binding of the azo ligand to the metal ions via two azo nitrogen atoms and protonated carboxylate O in a neutral tetradentate manner. Both IR and 1 H NMR spectra documented the involvement of the carboxylate group without proton displacement. The thermal studies pointed out that the complexes had higher thermal stability comparable with that of the free ligand. SEM images revealed the presence of the diazo ligand and its Cd(II) complex in a nanostructure form. The contact angle measurements proved that the Cd(II) complex can be considered as a superhydrophobic material. The molecular and electronic structure of H2 L and [Cd(H2 L)Cl2 ].H2 O were optimized theoretically, and the quantum chemical parameters were calculated. The biological activities of the ligand, as well as its metal complexes, have been tested in vitro against some bacteria and fungi species. The results showed that all the tested compounds have significant biological activities with different sensitivity levels. The binding between H2 L and its Cd(II) complex with receptors of the crystal structure of S. aureus (PDB ID: 3Q8U), crystal structure of protein phosphatase (PPZ1) of Candida albicans (PDB ID: 5JPE), receptors of breast cancer mutant oxidoreductase (PDB ID: 3HB5), and crystal structure of Escherichia coli (PDB ID: 3T88) was predicted and given in detail using molecular docking.